Fluid Mechanics Inspired Sequential Blade‐Coating for High‐Performance Large‐Area Organic Solar Modules. (1st May 2022) - Zhang, Ben; Yang, Fu; Chen, Shanshan; Chen, Haiyang; Zeng, Guang; Shen, Yunxiu; Li, Yaowen; Li, Yongfang
Abstract: Despite rapid advances in the field of organic solar cells (OSCs), high‐performance large‐scale OSC modules are limited. In this study, it is found that the non‐Newtonian fluid feature of conjugated polymer primarily causes the wedge‐shaped mass (donor and/or acceptor component)/phase distribution of blends in large‐scale blade coating, which results in the lower module efficiency. To address the critical issue in printing manufacturing, a reversible and sequential layer‐by‐layer (RS‐LBL) deposition method with sequential twice forward/reverse blade‐coating of polymer donor and forward blade‐coating of Y6 acceptor, is developed for precisely controlling fluid mechanics of PM6:Y6 active layer. Through using the RS‐LBL strategy, uniform morphology and favorable phase separation and crystallization are obtained in the 10 × 10 cm 2 active layer. As a result, the RS‐LBL‐based OSCs show excellent operational stability, and an outstanding PCE of 13.47% is achieved with significantly suppressed charge recombination losses in the 36 cm 2 large‐area OSC module, which represents the highest efficiency of binary solar modules with the area over 30 cm 2 . This study provides a feasible route for the next generation of high‐performance large‐area OSCs and OSC modules. Abstract : A fluid mechanics inspired reversible and sequential layer‐by‐layer (RS‐LBL) deposition method is developed, which provides a high‐performance 36 cm 2 OSC module with uniform mass (donor and/or acceptor component)/phase distribution of blends in large‐scale blade‐coating. As a result, a record PCE of 13.47% is achieved for binary solar modules with an active area over 30 cm 2 .